Effect of Feeding Fortified Milk Replacer on Dry Matter Intake and Nutrient Utilization in Crossbred Dairy Calves - Rajaram Karade, Rohini; Joseph Bunglavan, Surej; K, Ally; K, Shyama; Sasidharan, Manju; Mary Issac, Yancy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study was carried out to investigate the influence of fortified milk replacer on the growth performance and nutrient digestibility  of pre-ruminant HF crossbred dairy calves. Fourteen male and female crossbred calves were allocated at random to two groups, T1  (Control) and T2 (Treatment), each having seven calves. The T1 group received whole milk for 120 days, whereas the T2 group was offered  reconstituted fortified milk replacer with essential vitamins, minerals, amino acids, lysolecithin and probiotics to enhance nutrient  utilization, fat digestibility and gut health. Calves were fed at a rate of 1/10th of body weight for the first six weeks, 1/15th for the next four  weeks and 1/20th for the last two weeks, according to the feeding regimen. According to ICAR (2013) guidelines, both groups received  green fodder (Hybrid Napier CO3) and a calf starter (23% crude protein, 70% TDN) during the trial. Unlimited access to fresh drinking  water was provided. The two groups did not differ significantly (p>0.05) in terms of feed intake, growth performance, and digestibility  of dry matter and crude protein. However, the T2 group showed a significantly higher (p
Keywords: Crossbred calves; Growth performance; Digestibility; Economics; Fortified milk replacer